HUBUNGAN PENGETAHUAN TENTANG KANKER PAYUDARA DENGAN TINDAKAN MELAKUKAN SADARI PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS KABIL KOTA BATAM - Amelia, Cevy; Susanti, Rini (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
The breast self-examination (BSE or SADARI) is a self-examination to find out whether or not there is an abnormal lump in the breast, particulary, in the childbearing-aged women with the aim to anticipate the cancer. The purpose of this study is to assess the corelation of the breast cancer awereness and the application of BSE in the childbearing aged women in the Kabil Community health center 2017.This research is a quantitative research and the method of the research is analytic with the cross sectional approach applied in the Kabil Community health center on Tuesday 31st July 2017. The sampling technique is the accidental sampling with total of 92 samples. The result of the research is analyzed by using the cross-tabulated frequency distribution then tested with chi-square.From the 92 samples obtained that the number of the childbearing aged women with low awereness is 29 samples (31.5%), moderate awereness 54 samples (58.7%), and high awereness 9 samples (9.8%). Meanwhile the number of the childbearing aged women who apply the BSE is 25 samples (27.2%) and not aplly the BSE is 67 samples (72.8 %). The result shows that there is a positive correlation between the breast cancer awereness and the application of SADARI on the childbearing aged women in the Kabil Community health center. The chi square analysis result is p = 0.001. based on this study it is concluded that there is a corelation between the breast cancer awereness and the application of SADARI on the childbearing aged women in the Kabil Community health center 2017.